The Relationship Between Authoritarian Parenting and Aggressive Behavior of Adolescents in Nagari Bungo Tanjung - Sri Hartini; Eriana Alie; Jeeny March (World Psychology, 2022)
The subject in this thesis is the application of authoritarian parenting of parents so that adolescents have feelings of pressure and have high fear around parents, also causing adolescents to have aggressive behaviour in society and in peer environments. The purpose of this study was to find out how authoritarian parenting relationships with adolescent aggressive behaviour in Nagari Bungo Tanjung. The purpose of quantitative research is to the relationship between the two variables, developing and using mathematical models, theories and hypotheses related to natural phenomena.